Akcja Wyborcza Solidarność – brak marketingu politycznego i medialnego jako jedna z przyczyn upadku - Madera, Andrzej Józef (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
Although the Solidarity Election Action (AWS) had been the first impressive attempt to unite right-wing groupings after 1989 which was effected in practice, it failed to develop a united, coherent image for the purpose of contacts with the media throughout the whole period it was in power. Reality showed that right-wing politicians failed to take advantage of the assets of the new grouping. Incompetence of its leaders and absence of a coherent policy quickly overshadowed the success of the Solidarity Election Action. As a consequence, Solidarity Election Action has wasted an enormous chance and failed to become a united group of the Polish right wing. Leaders of individual organizations composing the AWS did not give up their leaders’ ambitions, which became particularly significant towards the end of theAWS-UW(Solidarity Election Action – Liberty Union) coalition, when the right-wing block was eroding rapidly.